Lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof

By embedding lithium manganese iron phosphate into the carbon frame, a specific structure of lithium manganese iron phosphate positive electrode material is prepared, which solves the problem of improving the capacity of existing materials, and achieves the improvement of high specific capacity and rate performance. It is suitable for high-demand applications such as electric vehicles.

CN119786595APending Publication Date: 2025-04-08EVE ENERGY CO LTD

Patent Information

Application Number
CN202412000210.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The capacity of existing lithium manganese iron phosphate cathode materials is difficult to effectively increase, resulting in poor performance in high-demand applications such as electric vehicles.

Method used

By embedding lithium manganese iron phosphate into the carbon frame, a lithium manganese iron phosphate positive electrode material with a specific particle size and porosity is prepared to form a three-dimensional interconnected pore structure, and the lithium storage capacity and conductivity of the material are improved.

Benefits of technology

The specific capacity and rate performance of lithium manganese iron phosphate positive electrode material is significantly improved, the diffusion path of lithium ions and the permeability of electrolyte are enhanced, and the energy density and cycle stability of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786595A_ABST
    Figure CN119786595A_ABST
Patent Text Reader

Abstract

The invention provides a lithium manganese iron phosphate positive electrode material as well as a preparation method and application thereof, and relates to the technical field of lithium ion batteries. The lithium manganese iron phosphate positive electrode material comprises a carbon framework and lithium manganese iron phosphate embedded in the carbon framework, the average particle size of the lithium manganese iron phosphate is 85-180 nm; the porosity of the lithium manganese iron phosphate positive electrode material is 20-36%, and the specific capacity of the lithium manganese iron phosphate positive electrode material can be effectively improved by designing the structure of the lithium manganese iron phosphate positive electrode material, so that the energy density of a battery is improved, and the application range of the battery is widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a lithium iron manganese phosphate positive electrode material and a preparation method and application thereof. Background Art

[0002] With the global energy crisis and increasing environmental awareness, the development of renewable energy and efficient energy storage technology have become core issues for achieving sustainable development. Among many energy storage technologies, lithium-ion batteries stand out for their excellent performance and have become one of the most widely used power sources for portable electronic devices, electric vehicles and large-scale energy storage systems. Among the various components of lithium-ion batteries, the positive electrode material determines the overall performance of the battery, and its specific capacity and rate performance are key parameters in practical applications.

[0003] So far, although LiNi 1-x-y Mn x Co y Layered oxide cathodes such as NCM can provide high specific capacity, but their volume and surface instability lead to poor cycle life and thermal stability. In addition, these layered oxide cathodes usually contain a large amount of Ni or Co, which increases their cost and environmental impact. In this regard, LiFePO4 (LFP) is valued due to its excellent capacity, low cost and high thermal stability. However, compared with layered oxide cathode materials, the low capacity of LFP makes it difficult to meet the demanding requirements of electric vehicles. Studies have shown that by using Mn 2+ Partially replace Fe 2+ Formation of LiMn x Fe 1-x PO4(LMFP), can make LMFP have higher capacity. Theoretically, compared with LFP, the capacity of LMFP can be increased by 10% to 20%, but due to Mn 2+ / 3+ Due to the kinetic limitations of redox, this improvement is difficult to achieve in practice, which leads to the low actual capacity of LMFP with high Mn content (over 50%). These kinetic limitations come from the 3+ Jahn-Teller distortion, resulting in increased lattice strain and Li + Deterioration of diffusion dynamics. Summary of the invention

[0004] The main purpose of the present application is to provide a lithium iron manganese phosphate positive electrode material and a preparation method and application thereof, so as to solve the problem that the capacity of the lithium iron manganese phosphate positive electrode material in the prior art is difficult to effectively improve.

[0005] In order to achieve the above-mentioned purpose, according to one aspect of the present application, a lithium iron manganese phosphate positive electrode material is provided, wherein the lithium iron manganese phosphate positive electrode material comprises a carbon framework (CNWs) and lithium iron manganese phosphate (LMFP) embedded in the carbon framework; the average particle size of the lithium iron manganese phosphate is 85nm~180nm; the porosity of the lithium iron manganese phosphate positive electrode material is 20%~36%.

[0006] Furthermore, taking the mass fraction of the lithium iron manganese phosphate positive electrode material as 100%, the mass fraction of the lithium iron manganese phosphate is 70% to 93%.

[0007] Furthermore, the carbon framework is doped with nitrogen, and the mass fraction of the nitrogen is 0.2% to 0.5% based on the mass fraction of the lithium manganese iron phosphate positive electrode material being 100%.

[0008] Furthermore, the specific surface area of ​​the lithium manganese iron phosphate cathode material is 85m 2 / g~140m 2 / g.

[0009] Furthermore, the average pore size of the lithium manganese iron phosphate positive electrode material is 30nm to 50nm.

[0010] Furthermore, the D50 particle size of the lithium manganese iron phosphate positive electrode material is 3 μm to 7.5 μm.

[0011] Furthermore, the general chemical formula of lithium manganese iron phosphate is LiFe x Mn y PO4, wherein x is 0.2 to 0.6 and y is 0.4 to 0.8.

[0012] According to another aspect of the present application, a method for preparing a lithium manganese iron phosphate positive electrode material is provided, comprising the following steps:

[0013] S1, mixing an iron salt, a manganese salt, an organic ligand and water to obtain a first mixture;

[0014] S2, subjecting the first mixture to a hydrothermal reaction, filtering, and washing to obtain a hydrothermal reaction product;

[0015] S3, dispersing the hydrothermal reaction product in a first solvent to obtain a second mixture; dissolving a lithium source and a phosphorus source in the second solvent to obtain a first solution;

[0016] S4, mixing the second mixture and the first solution to obtain a third mixture, stirring and drying the third mixture to obtain a solid product;

[0017] S5, performing a first calcination on the solid product in a reducing atmosphere to obtain the lithium manganese iron phosphate positive electrode material.

[0018] Furthermore, in S1, the anion in the iron salt is any one of nitrate ion, nitrite ion, sulfate ion, chloride ion, bromide ion and iodide ion.

[0019] Furthermore, in S1, the anion in the manganese salt is any one of nitrate ion, nitrite ion, sulfate ion, chloride ion, bromide ion and iodide ion.

[0020] Further, the organic ligand is any one of 1,4-terephthalic acid (BDC), 1,3,5-benzenetricarboxylic acid (BTC), and 1,2,4,5-benzenetetracarboxylic acid (BTEC); preferably, the organic ligand is 1,3,5-benzenetricarboxylic acid.

[0021] Furthermore, in S1, the mass ratio of iron salt, manganese salt, organic ligand and water is (1-2): (1-2): (0.9-1.8): (80-320).

[0022] Furthermore, in S2, the temperature of the hydrothermal reaction is 140°C to 200°C, and the time of the hydrothermal reaction is 12h to 15h.

[0023] Furthermore, in S2, the washing method is: first washing with deionized water at 70°C to 90°C for 3h to 5h, and then washing with ethanol at 45°C to 75°C for 3h to 5h.

[0024] Furthermore, in S2, the product is further purified after washing to obtain a hydrothermal reaction product; the purification method is: washing with an ammonium fluoride aqueous solution at 60° C. to 80° C. for 3 h to 5 h.

[0025] Furthermore, the first solvent and the second solvent are each independently selected from at least one of ethanol, propanol, and n-butanol.

[0026] Furthermore, the reducing atmosphere is a mixture of hydrogen and inert gas, and the volume ratio of hydrogen to inert gas is 1:(4-9).

[0027] Furthermore, the temperature of the first calcination is 500° C. to 650° C., and the time of the first calcination is 5 h to 6 h.

[0028] Further, in S5, after the first calcination is completed, the calcined product and C3N3(NH2)3 are dispersed in a third solvent, stirred, dried, and subjected to a second calcination under an inert atmosphere to obtain the lithium manganese iron phosphate positive electrode material.

[0029] Furthermore, in S5, the temperature of the second calcination is 450° C. to 600° C., and the time of the second calcination is 4 h to 5 h.

[0030] According to another aspect of the present application, there is provided an application of the above-mentioned lithium iron manganese phosphate positive electrode material or the lithium iron manganese phosphate positive electrode material prepared by the above-mentioned preparation method in a lithium-ion battery; for example, a positive electrode sheet is prepared using the above-mentioned lithium iron manganese phosphate positive electrode material.

[0031] By applying the technical solution of the present application, the lithium iron manganese phosphate positive electrode material includes a carbon frame and lithium iron manganese phosphate embedded in the carbon frame. By limiting the D50 particle size of the lithium iron manganese phosphate and the porosity of the lithium iron manganese phosphate positive electrode material, a three-dimensional interconnected pore structure can be formed inside the lithium iron manganese phosphate positive electrode material. On the one hand, the diffusion path length of lithium ions can be significantly shortened to provide a higher lithium storage capacity. On the other hand, the electrolyte can be easily penetrated to ensure close contact between the lithium iron manganese phosphate and the electrolyte, which is convenient for the rapid transfer of lithium ions. This is beneficial to improving the specific capacity of the lithium iron manganese phosphate positive electrode material, and then improving the energy density of the battery using it as the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The drawings constituting part of the present application are used to provide a further understanding of the present application. The exemplary embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0033] Figure 1 XRD diffraction patterns of MIL-100, MIL-101 and MIL-82 in Examples 1, 3 and 4 of the present application;

[0034] Figure 2 XRD diffraction patterns of LMFP / CNWs in Example 1 and LMFP / N-CNWs in Example 2 of the present application;

[0035] Figure 3 The SEM and EDS surface scans of MIL-100, MIL-101, and MIL-82 in Examples 1, 3, and 4 of the present application, (a) is a SEM image of MIL-100, (b) is an EDS surface scan of the Fe element in MIL-100, and (c) is an EDS surface scan of the Mn element in MIL-100; (d) is a SEM image of MIL-101, (e) is an EDS surface scan of the Fe element in MIL-101, and (f) is an EDS surface scan of the Mn element in MIL-101; (h) is a SEM image of MIL-82, (i) is an EDS surface scan of the Fe element in MIL-82, and (j) is an EDS surface scan of the Mn element in MIL-82;

[0036] Figure 4The SEM images of MIL-100, LMFP / CNWs in Example 1 and LMFP / N-CNWs in Example 2 of the present application; wherein (a) is the SEM image of MIL-100 in Example 1, (b) is the SEM image of LMFP / CNWs in Example 1, and (c) is the SEM image of LMFP / N-CNWs in Example 2;

[0037] Figure 5 The pore size distribution and N2 adsorption-desorption isotherm diagram of MIL-Fe / Mn, LMFP / CNWs in Example 1 of the present application and LMFP / N-CNWs in Example 2;

[0038] Figure 6 The XPS graphs of LMFP / CNWs in Example 1 and LMFP / N-CNWs in Example 2 of the present application; wherein (a) is a wide XPS spectrum of LMFP / CNWs, (b) is a wide XPS spectrum of LMFP / N-CNWs, and (c) is a high-resolution XPS spectrum of LMFP / N-CNWs;

[0039] Figure 7 The discharge capacity / cycle number curve of the button cell composed of the lithium manganese iron phosphate positive electrode material in Example 1 and Example 2 of the present application;

[0040] Figure 8 The EIS impedance diagram of the button cell composed of the lithium manganese iron phosphate positive electrode material in Example 1 and Example 2 of the present application; wherein (a) is the Nquist diagram, (b) is the Bode diagram, and (c) is the corresponding fitting circuit diagram. DETAILED DESCRIPTION

[0041] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its application or use. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0042] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0043] Unless otherwise specifically stated, the relative arrangement, numerical expressions and numerical values ​​of the parts and steps set forth in these embodiments do not limit the scope of the present application. At the same time, it should be understood that, for ease of description, the sizes of the various parts shown in the accompanying drawings are not drawn according to the actual proportional relationship. The technology, method and equipment known to those of ordinary skill in the relevant field may not be discussed in detail, but in appropriate cases, the technology, method and equipment should be considered as a part of the authorization specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values. It should be noted that similar reference numerals and letters represent similar items in the following drawings, so that once a certain item is defined in an accompanying drawing, it does not need to be further discussed in subsequent drawings.

[0044] In the description of the present application, it should be understood that the directions or positional relationships indicated by directional words such as "front, back, up, down, left, right", "lateral, vertical, perpendicular, horizontal" and "top, bottom" are usually based on the directions or positional relationships shown in the drawings, and are only for the convenience of describing the present application and simplifying the description. Unless otherwise specified, these directional words do not indicate or imply that the device or element referred to must have a specific direction or be constructed and operated in a specific direction, and therefore cannot be understood as limiting the scope of protection of the present application; the directional words "inside and outside" refer to the inside and outside relative to the contours of each component itself.

[0045] As described in the background technology of the present application, compared with the lithium iron phosphate positive electrode material, the specific capacity of the lithium iron manganese phosphate positive electrode material has not been significantly improved. In order to solve the above technical problems, in a typical embodiment of the present application, a lithium iron manganese phosphate positive electrode material is provided, and the lithium iron manganese phosphate positive electrode material includes a carbon frame and lithium iron manganese phosphate embedded in the carbon frame; the average particle size of the lithium iron manganese phosphate is 85nm~180nm; the porosity of the lithium iron manganese phosphate positive electrode material is 20%~36%.

[0046] By embedding lithium iron manganese phosphate into the carbon framework, the carbon framework can serve as a conductive substrate, which can effectively enhance the electronic conductivity of the lithium iron manganese phosphate positive electrode material. Limiting the average particle size of lithium iron manganese phosphate can provide more reactive sites, increase the contact area with the electrolyte, and help improve the lithium storage capacity of the material. Controlling the size within the above range can also reduce the lattice strain during the cycle and improve its stability. Controlling the porosity of the lithium iron manganese phosphate positive electrode material within the above range helps to construct a three-dimensional interconnected pore system, which can ensure good contact between the lithium iron manganese phosphate nanoparticles and the carbon framework on the one hand, and on the other hand, enable the electrolyte and the material surface to be in close contact, improve electronic and ionic conductivity, and improve the specific capacity of the lithium iron manganese phosphate positive electrode material.

[0047] In some embodiments, based on the mass fraction of the lithium iron manganese phosphate positive electrode material being 100%, the mass fraction of the lithium iron manganese phosphate is 70% to 93%.

[0048] In lithium iron phosphate positive electrode materials, the mass fraction of lithium iron phosphate directly affects its lithium storage capacity. The increase in the content of lithium iron phosphate means that more lithium ions can participate in the electrochemical reaction, improving the specific capacity and energy output of the battery, but too much lithium iron phosphate will affect the penetration of the electrolyte and the diffusion rate of lithium ions. Controlling the mass fraction of lithium iron phosphate within the above range can make the lithium iron phosphate positive electrode material have good specific capacity and cycle stability.

[0049] In some embodiments, the carbon framework is doped with nitrogen, and the mass fraction of the nitrogen is 0.2% to 0.5% based on the mass fraction of the lithium manganese iron phosphate positive electrode material being 100%.

[0050] Doping nitrogen into the carbon framework is based on the principles of material modification and electronic structure regulation. The formed nitrogen-doped carbon framework (N-CNMs) not only provides a continuous path for electronic conduction, but also enhances the charge transfer ability and ion conductivity of the material by changing the electronic state of carbon, which helps to improve the specific capacity and rate performance of lithium manganese iron phosphate positive electrode materials.

[0051] In some embodiments, the specific surface area of ​​the lithium manganese iron phosphate positive electrode material is 85m 2 / g~140m 2 / g.

[0052] Controlling the specific surface area of ​​the lithium iron manganese phosphate positive electrode material within the above range is beneficial to the rapid transmission of lithium ions, while not being too dense to affect the mechanical strength and chemical stability of the material.

[0053] In some embodiments, the average pore size of the lithium manganese iron phosphate positive electrode material is 30 nm to 50 nm.

[0054] Controlling the average pore size of the lithium iron manganese phosphate positive electrode material within the above range can optimize the diffusion path of the lithium-ion battery and improve the battery's rate performance; it also helps to provide a buffer space for the volume change of the lithium iron manganese phosphate positive electrode material during the charge and discharge process, thereby improving its cycle life.

[0055] In some embodiments, the D50 particle size of the lithium manganese iron phosphate positive electrode material is 3 μm to 7.5 μm.

[0056] Controlling the D50 particle size of the lithium iron manganese phosphate positive electrode material within the above range helps to significantly shorten the diffusion path length of lithium ions in the positive electrode material, so that lithium ions can migrate faster inside the material, reducing the resistance to charge transfer, thereby improving the rate performance of the battery; in addition, the particle size also has a great influence on the stability of the structure and the dispersibility of the positive electrode material in the subsequent pulping process. By controlling the D50 particle size, the lithium iron manganese phosphate positive electrode material and the conductive agent and binder can be more evenly dispersed to form a stable electrode structure, which is beneficial to improving the thermal stability and safety of the battery.

[0057] In some embodiments, the chemical formula of lithium manganese iron phosphate is LiFe x Mn y PO4, wherein x is 0.2 to 0.6 and y is 0.4 to 0.8.

[0058] The doping ratio of Fe and Mn can regulate the redox potential of LMFP, thereby affecting the discharge voltage platform of the material and improving the energy density of the battery; in addition, the present application can also improve the cycle life of the battery by regulating the ratio of each element.

[0059] In another typical embodiment of the present application, a method for preparing a lithium manganese iron phosphate positive electrode material is provided, comprising the following steps:

[0060] S1, mixing an iron salt, a manganese salt, an organic ligand and water to obtain a first mixture;

[0061] S2, subjecting the first mixture to a hydrothermal reaction, filtering, and washing to obtain a hydrothermal reaction product;

[0062] S3, dispersing the hydrothermal reaction product in a first solvent to obtain a second mixture; dissolving a lithium source and a phosphorus source in the second solvent to obtain a first solution;

[0063] S4, mixing the second mixture and the first solution to obtain a third mixture, stirring and drying the third mixture to obtain a solid product;

[0064] S5, performing a first calcination on the solid product in a reducing atmosphere to obtain the lithium manganese iron phosphate positive electrode material.

[0065] The present application adopts a hydrothermal reaction to synthesize a bimetallic organic framework (MIL-Fe / Mn) with high purity and good crystallinity. The bimetallic organic framework has strong structural integrity and thermal stability. After calcination, the bimetallic organic framework structure collapses, and the organic ligands are reduced to a porous, three-dimensional interconnected carbon framework. At the same time, Li + and (PO4) 3+It reacts with MIL-Fe / Mn to form LMFP particles, and in situ constructs a lithium iron manganese phosphate positive electrode material including a carbon framework and lithium iron manganese phosphate embedded in the carbon framework; in the lithium iron manganese phosphate positive electrode material, the D50 particle size and porosity of the lithium iron manganese phosphate are moderate, which can improve the electronic conductivity and ion diffusion of the lithium iron manganese phosphate positive electrode material and increase the specific capacity of the lithium iron manganese phosphate positive electrode material.

[0066] In some embodiments, in S1, the anion in the iron salt is any one of nitrate ion, nitrite ion, sulfate ion, chloride ion, bromide ion, and iodide ion, such as Fe(NO3)3·9H2O, FeCl3·6H2O, etc.

[0067] In some embodiments, in S1, the anion in the manganese salt is any one of nitrate ion, nitrite ion, sulfate ion, chloride ion, bromide ion, and iodide ion, such as Mn(NO3)2·4H2O, MnCl2·4H2O, etc.

[0068] In some embodiments, in S1, the organic ligand is any one of 1,4-terephthalic acid, 1,3,5-benzenetricarboxylic acid, and 1,2,4,5-benzenetetracarboxylic acid, preferably 1,3,5-benzenetricarboxylic acid.

[0069] In some embodiments, the lithium source and the phosphorus source are each independently at least one of lithium dihydrogen phosphate and lithium hydrogen phosphate, and the selection of the above components will not introduce impurities.

[0070] The lithium iron manganate positive electrode material prepared by selecting the above-mentioned specific types of iron salts, manganese salts and organic ligands has a stable structure and uniform composition, which is beneficial to improving the diffusion rate of lithium ions and the electrochemical reaction activity.

[0071] In some embodiments, the mass ratio of iron salt, manganese salt, organic ligand and water is (1-2): (1-2): (0.9-1.8): (80-320).

[0072] Controlling the mass ratio of iron salt, manganese salt, organic ligand and water within a specific range has a great effect on the uniformity and structural stability of the lithium iron manganese phosphate positive electrode material. In addition, it can make the ratio of each element in the lithium iron manganese phosphate positive electrode material within the optimal range, which can further improve the electrochemical performance of the lithium iron manganese phosphate positive electrode material.

[0073] In some embodiments, in S2, the temperature of the hydrothermal reaction is 140° C. to 200° C., and the time of the hydrothermal reaction is 12 h to 15 h.

[0074] Under the above conditions, iron salts, manganese salts and organic ligands can fully react to form MIL-Fe / Mn with high crystallinity, which plays a great role in improving the structural stability of lithium manganese iron phosphate positive electrode materials.

[0075] In some embodiments, in S2, the washing method is: first washing with deionized water at 70°C to 90°C for 3h to 5h, and then washing with ethanol at 45°C to 75°C for 3h to 5h. The above method can be used to improve the purity of the hydrothermal reaction product. Further, after washing with ethanol, washing with an ammonium fluoride aqueous solution at 60°C to 80°C for 3h to 5h. Ammonium fluoride can react with metal ion impurities in the hydrothermal reaction product to achieve the purpose of further purification and impurity removal.

[0076] In some embodiments, the first solvent and the second solvent are each independently selected from at least one of ethanol, propanol, and n-butanol. The above solvents can effectively dissolve the hydrothermal reaction product, the lithium source, and the phosphorus source, and help improve the uniformity of the lithium iron manganese phosphate positive electrode material.

[0077] In some embodiments, the reducing atmosphere is a mixture of hydrogen and an inert gas, wherein the volume ratio of hydrogen to the inert gas is 1:(4-9), wherein the inert gas is at least one of nitrogen, argon, and the like.

[0078] Calcination under the above conditions can fully reduce the MIL-Fe / Mn, and the safety of the production process is relatively high.

[0079] In some embodiments, the temperature of the first calcination is 500° C. to 650° C., and the time of the first calcination is 5 h to 6 h.

[0080] By calcining under the above conditions, MIL-Fe / Mn can be reduced to a lithium manganese iron phosphate positive electrode material having high structural stability and including a carbon framework and lithium manganese iron phosphate embedded in the carbon framework.

[0081] In some embodiments, in S5, after the calcination is completed, the calcined product and C3N3(NH2)3 are dispersed in a third solvent, stirred, dried, and subjected to a second calcination under an inert atmosphere to obtain the lithium manganese iron phosphate positive electrode material.

[0082] By calcining under the above conditions, the carbon framework of the prepared lithium manganese iron phosphate positive electrode material is doped with nitrogen, which is beneficial to improving the conductivity and ion transport performance of the lithium manganese iron phosphate positive electrode material.

[0083] In some embodiments, the third solvent is at least one of ethanol, propanol, and n-butanol. C3N3(NH2)3 and the first calcined product can be fully dissolved in the above solvent.

[0084] In some embodiments, in S5, the temperature of the second calcination is 450° C. to 600° C., and the time of the second calcination is 4 h to 5 h.

[0085] Under the above conditions, the nitrogen doping efficiency is high and the stability is good. The formation of the nitrogen-doped carbon framework reduces the lattice strain during the cycle process, thereby improving the cyclic stability of the material.

[0086] In another typical embodiment of the present application, a lithium iron manganese phosphate positive electrode material in the above embodiment or a lithium iron manganese phosphate positive electrode material prepared by the preparation method in the above embodiment is provided in a lithium ion battery. Specifically, the present application provides a positive electrode plate, the positive electrode plate comprising a current collector and the lithium iron manganese phosphate positive electrode material, a conductive agent and a binder coated on the surface of the current collector.

[0087] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0088] Example 1

[0089] An embodiment of the lithium iron manganese phosphate positive electrode material of the present application, the preparation method of the lithium iron manganese phosphate positive electrode material of the present embodiment is as follows:

[0090] S1, Fe(NO3)3·9H2O, Mn(NO3)2·4H2O, 1,3,5-benzenetricarboxylic acid and water are mixed in a mass ratio of 1:1:0.9:200, and stirred at room temperature for 1 h to obtain a first mixture;

[0091] S2, transferring the first mixture into a hydrothermal reactor, heat treating at 160°C for 12h, filtering the obtained suspension after the reaction, washing with deionized water at 80°C for 3h, washing with ethanol at 65°C for 3h, until there are no colored impurities in the filtrate, purifying with 70°C ammonium fluoride aqueous solution for 3h, drying in air at 80°C for 12h, and obtaining the hydrothermal reaction product bimetallic organic framework MIL-Fe / Mn, named MIL-100;

[0092] S3, dispersing 6.51 g of MIL-Fe / Mn in 50 mL of ethanol to obtain a second mixture; dissolving 4.08 g of lithium dihydrogen phosphate in 100 mL of ethanol to obtain a first solution, wherein the molar ratio of Mn+Fe to Li is controlled to be 1:1;

[0093] S4, mixing the second mixture and the first solution to obtain a third mixture, stirring the third mixture at room temperature for 24 hours, and then evaporating at 80° C. for 4 hours to obtain a solid product;

[0094] S5, calcining the solid product in a mixed gas with a volume ratio of hydrogen to argon of 1:9, with a heating rate of 2°C / min, heating to 600°C and then keeping the temperature for 5 hours to obtain a lithium manganese iron phosphate positive electrode material LMFP / CNWs.

[0095] Example 2

[0096] An embodiment of the lithium iron manganese phosphate positive electrode material of the present application, the preparation method of the lithium iron manganese phosphate positive electrode material of this embodiment is different from that of embodiment 1 in that:

[0097] After obtaining the lithium manganese iron phosphate positive electrode material LMFP / CNWs, 0.4672g C3N3(NH2)3 and 4g LMFP / CNWs in Example 1 were mixed in 60mL ethanol, then stirred at 60°C for 24h, vacuum dried at 80°C for 10h, and finally calcined at 600°C in a nitrogen atmosphere for 4h to obtain the lithium manganese iron phosphate positive electrode material LMFP / N-CNWs.

[0098] Embodiment 3-4

[0099] The embodiments of the lithium iron manganese phosphate positive electrode material of the present application, the preparation method of the lithium iron manganese phosphate positive electrode material described in embodiments 3 to 4 is different from that in embodiment 1 only in that the types of organic ligands are different, as follows:

[0100] In Example 3, 1,4-terephthalic acid was used instead of 1,3,5-benzenetricarboxylic acid, and the obtained bimetallic organic framework was named MIL-101;

[0101] In Example 4, 1,2,4,5-benzenetetracarboxylic acid was used instead of 1,3,5-benzenetricarboxylic acid, and the obtained bimetallic organic framework was named MIL-82.

[0102] Embodiments 5 to 8

[0103] The embodiments of the lithium iron manganese phosphate positive electrode material of the present application, the preparation method of the lithium iron manganese phosphate positive electrode material described in embodiments 5 to 8 is different from that in embodiment 1 only in that the mass ratio of each component in S1 is different, as follows:

[0104] In Example 5, the mass ratio of Fe(NO3)3·9H2O, Mn(NO3)2·4H2O, 1,3,5-benzenetricarboxylic acid and water is 1:1:1.2:200;

[0105] In Example 6, the mass ratio of Fe(NO3)3·9H2O, Mn(NO3)2·4H2O, 1,3,5-benzenetricarboxylic acid and water is 1:1:1.5:200;

[0106] In Example 7, the mass ratio of Fe(NO3)3·9H2O, Mn(NO3)2·4H2O, 1,3,5-benzenetricarboxylic acid and water is 1:1:0.6:200;

[0107] In Example 8, the mass ratio of Fe(NO3)3·9H2O, Mn(NO3)2·4H2O, 1,3,5-benzenetricarboxylic acid and water is 1:1:2:200.

[0108] Comparative Example 1

[0109] The comparative example of the lithium iron manganese phosphate positive electrode material of the present application, the preparation method of the lithium iron manganese phosphate positive electrode material is different from that of Example 1 only in that the average particle size of the prepared lithium iron manganese phosphate is different, as follows:

[0110] In Comparative Example 1, Fe(NO3)3·9H2O, Mn(NO3)2·4H2O, 1,3,5-benzenetricarboxylic acid and water were mixed in a mass ratio of 1:1:0.9:200, and stirred at room temperature for 1 hour to obtain a first mixture;

[0111] The first mixture was transferred into a hydrothermal reactor and heat treated at 250° C. for 12 h.

[0112] Performance Testing

[0113] 1. Structural characterization:

[0114] (1) The surface morphology and energy dispersive X-ray spectra of MIL-Fe / Mn and lithium manganese iron phosphate cathode materials were recorded using a field emission scanning electron microscope (SEM, S-4800) and its attached energy dispersive spectrometer (EDX, Genesis XM2System 60). The microstructure and particle size (median particle size, D50) of the powders can be obtained from the SEM images, and the elemental composition, content and distribution of the samples can be obtained from the X-ray spectra.

[0115] (2) The crystal structure and phase composition of the samples were identified using an X-ray diffractometer (XRD, PHI-5400) at 40 kV and Cu Kα (wavelength λ = 0.15418 nm) with a diffraction angle (2θ) ranging from 10° to 60°;

[0116] (3) The elemental composition and content of the samples were determined using a K-Alpha X-ray photoelectron spectrometer (XPS, Thermo ESCALAB 250XI), and the relative atomic ratios of C, N, and O in the samples were obtained. Al Kα monochromatic radiation was used as the X-ray source (hν=1468 eV), the voltage was 16 kV, the beam spot diameter was 650 μm, and the charge calibration was performed using C1s=284.8 eV as the standard.

[0117] (4) A thermogravimetric analyzer (TG, SHIMADZUTG-50, Japan) was used to determine the mass fraction of carbon in the sample. The sample was heated from 20°C to 700°C under dry air at a rate of 2°C / min. The mass fraction of carbon in the sample and the mass fraction of lithium iron manganese phosphate were calculated based on the weight gain difference in the thermogravimetric curve, and the mass fraction of nitrogen was determined in combination with the relative atomic ratio of C and N.

[0118] (5) The specific surface area, pore size, and total pore volume of the sample (single-point method) were determined using a surface area and pore size analyzer (BET, Quantachrome Instruments-Nove 2000e, USA) by the N2 adsorption-desorption method, and the porosity of the sample was calculated.

[0119] 2. Electrochemical performance test

[0120] The lithium manganese iron phosphate positive electrode materials in the embodiment and the comparative example are made into CR-2032 button batteries, and the specific steps are as follows:

[0121] The positive electrode material of lithium manganese iron phosphate, the conductive agent carbon black and the binder polyvinylidene fluoride were added to N-methylpyrrolidone in a mass ratio of 8:1:1, stirred and dispersed in a homogenizer, coated on aluminum foil, and baked in an oven at 85°C for 30 minutes. 2 The disc was weighed and recorded, and then baked in a vacuum oven at 120°C for 8 h to obtain the positive electrode sheet as the working electrode.

[0122] Lithium metal was used as the counter / reference electrode, the diaphragm was Celgard, the solute of the electrolyte was LiPF6, and the solvent was a mixture of dimethyl carbonate and ethylene carbonate in a mass ratio of 1:1.1, wherein the concentration of LiPF6 was 1M.

[0123] (1) Rate performance: Tested by Xinwei battery charge and discharge tester (5V 10mA), ambient temperature is 25℃, between 2.3~4.5V vs.Li / Li + The voltage window of each button cell was continuously charged and discharged by applying different current densities. Before the test, the theoretical capacity of each button cell was calculated to obtain the current at different charge and discharge rates. The charge and discharge tests were all carried out in CC-CV mode, and the current was carried out in steps of 0.1C, 0.2C, 0.5C, 1C, 2C, 5C and 10C, with each cycle number being 3 to 10 cycles.

[0124] (2) EIS tests were performed on each button cell using a two-electrode system on an IM6ex electrochemical workstation (ZAHNER electric, Germany). Before the test, the cells were cycled at 0.2C for 3 cycles, and then the state of charge (SOC) was adjusted to 50% by charge and discharge to ensure that the positive and negative electrodes inside the battery were fully wetted and transformed into non-inert electrodes. The ambient temperature was 25°C, the voltage was set to 4 V, the AC voltage amplitude was 5 mV, and the frequency was 10 -2 ~10 6 Hz.

[0125] (3) The Nyquist curve of EIS shows a semicircular feature at high frequencies and a straight line at low frequencies, which can be used to analyze the solution resistance (Rs), the charge transfer resistance (Rct) at the electrode / electrolyte interface, and the lithium ion diffusion resistance (Zw). The equivalent circuit diagram is shown in the figure below. Figure 8 As shown in Figure (c), the Li of the sample is calculated by combining the EIS impedance diagram fitting data and the following formula + Diffusion coefficient

[0126]

[0127] Where R is the gas constant (8.314 J·K -1 mol -1 ), T is the absolute temperature (298K), F is the Faraday constant (96500C / mol), A is the effective working area of ​​the electrode (1.13097cm 2 ), n is the half-reaction electron transport ratio in the redox process (n = 1), C is the Li + Concentration (1 mol cm -3 ), σ is the Warburg factor, which is the relationship between Z′ and ω -1 / 2 The function of is obtained, ω(Hz) is the frequency.

[0128] The performance test results are as follows:

[0129] Table 1 shows the performance test results of lithium manganese iron phosphate positive electrode materials in the embodiments and comparative examples.

[0130] Table 1

[0131]

[0132]

[0133] Figure 1Figure 3 is the XRD diffraction pattern of MIL-100, MIL-101 and MIL-82. It can be seen from the figure that the diffraction peak intensity of MIL-100 (Fe-Mn, BTC) is higher. In addition, according to the Debye-Scherrer equation (D=kλ / βcosθ), D is the average grain diameter, λ is the wavelength of the incident X-ray, θ is the diffraction angle, β is the full width at half maximum of the diffraction, k is the Scherrer constant, and 0.89 is taken to calculate the grain size of each organic ligand. The results show that the grain size of MIL-101 is 179nm, the grain size of MIL-82 is 264nm, and MIL-100 has the smallest grain size of 155nm. The strength and hardness of its framework will be improved, and it will also help to form a more stable microporous structure and enhance the kinetic properties of lithium manganese iron phosphate positive electrode materials.

[0134] Figure 2 The XRD diffraction patterns of LMFP / CNWs in Example 1 and LMFP / N-CNWs in Example 2 show that the diffraction peaks of both are similar to those of orthorhombic olivine LiMn with Pnma space group. 0.5 Fe 0.5 PO4 (ICDD PDF No.42-0580), which indicates that pure phase LMFP active materials can be successfully prepared using bimetallic organic frameworks as templates. It also reveals that doping nitrogen in CNWs has no effect on the crystal structure of LMFP.

[0135] Figure 3 The SEM and EDS surface scanning energy spectrum of MIL-100, MIL-101, and MIL-82, (a) is the SEM image of MIL-100, (b) is the EDS surface scanning image of the Fe element in MIL-100, and (c) is the EDS surface scanning image of the Mn element in MIL-100; (d) is the SEM image of MIL-101, (e) is the EDS surface scanning image of the Fe element in MIL-101, and (f) is the EDS surface scanning image of the Mn element in MIL-101; (h) is the SEM image of MIL-82, (i) is the EDS surface scanning image of the Fe element in MIL-82, and (j) is the EDS surface scanning image of the Mn element in MIL-82. As can be seen from the figure, all samples are micron-level materials, showing a regular cubic three-dimensional structure, with a smooth and clean surface. The EDS results show that the metal Fe and Mn can be evenly distributed on the particle surface.

[0136] Figure 4Figure 1 is a SEM image, where (a) is the SEM image of MIL-100 in Example 1, (b) is the SEM image of LMFP / CNWs in Example 1, and (c) is the SEM image of LMFP / N-CNWs in Example 2. It can be seen from the figure that although the skeleton structure of MIL-100 is completely destroyed during the pyrolysis process, LMFP / CNWs basically maintains the complete morphology and size parameters of MIL-100. The high-magnification SEM image of the inserted part in (b) shows that the nanoscale LMFP particles are uniformly incorporated into the staggered guest carbon framework. During the pyrolysis process, Li + and (PO4) 3+ The LMFP particles were formed on the secondary building blocks of MIL-100 by impregnation into the pores and channels of the bimetallic organic framework. The carbon framework produced by carbonization of organic ligands in MIL-100 was polymerized in situ on the surface of the generated LMFP particles, which may hinder their growth during heat treatment. At the same time, a large number of micropores were generated inside the LMFP particles, further constructing a three-dimensional interconnected pore system. After doping nitrogen into the carbon framework, its structure changed little.

[0137] Figure 5 The pore size distribution and N2 adsorption-desorption isotherms of MIL-Fe / Mn, LMFP / CNWs in Example 1 and LMFP / N-CNWs in Example 2 show that the average pore sizes of BJH adsorption of LMFP / CNWs in Example 1 and LMFP / N-CNWs in Example 2 are 40.5 nm and 42.3 nm, respectively. This structure helps to increase the contact area between the electrode material and the electrolyte.

[0138] Figure 6 The XPS graphs of LMFP / CNWs in Example 1 and LMFP / N-CNWs in Example 2, wherein (a) is the wide XPS spectrum of LMFP / CNWs, (b) is the wide XPS spectrum of LMFP / N-CNWs, and (c) is the high-resolution XPS spectrum of LMFP / N-CNWs. It can be seen from (a) and (b) that the binding energies are approximately 56.4 eV, 132.7 eV, 285.5 eV, 398.4 eV, 531.2 eV, 641.4 eV, and 709.6 eV, corresponding to Li 1s, P 2p, C 1s, N 1s, O1s, Mn 2P, respectively. 3 / 2 and Fe 2P 3 / 2Compared with the measured spectrum of LMFP / CNWs sample, it can be clearly observed that the new binding energy of LMFP / N-CNWs sample is about 399 eV, which can be attributed to N1s. As shown in Figure (c), it can be decomposed into three components centered at 398.3 eV, 399.5 eV, and 401 eV, corresponding to the pyridine type, pyrrole type, and graphite type of N atoms, respectively. This result shows that the N element is successfully doped into LMFP / CNWs, which is beneficial to improve the electron transfer rate of lithium manganese iron phosphate cathode material, thereby improving its electrochemical performance.

[0139] Table 2 shows the electrochemical performance test results of button cells made with the lithium manganese iron phosphate positive electrode materials in Examples 1 to 8 and Comparative Example 1.

[0140] Table 2

[0141]

[0142]

[0143] It can be seen from Table 2 that the lithium manganese iron phosphate positive electrode material in the embodiment of the present application has a higher discharge specific capacity, better rate performance, and a high ion diffusion coefficient, and has good electrochemical properties.

[0144] Figure 7 The discharge capacity / cycle number curve of the button cell composed of the lithium manganese iron phosphate positive electrode material in Example 1 and Example 2. It can be seen from the figure that at 0.1C and 0.5C rates, the discharge specific capacities of LMFP / CNWs and LMFP / N-CNWs are not much different, but when the rate increases to 10C, LMFP / N-CNWs still shows a higher specific capacity, about 82.14% of that at 0.1C, which shows that after doping with nitrogen, the rate performance has been significantly improved.

[0145] Figure 8 The EIS spectra of button cells composed of the lithium manganese iron phosphate positive electrode materials in Examples 1 and 2 are shown; wherein (a) is the Nquist diagram, (b) is the Bode diagram, and (c) is the corresponding fitting circuit diagram. The Nquist diagram shows that the curve is composed of a downward depressed semicircle at high frequency and a straight line at low frequency. In the high frequency region, the real impedance axis intercepts of the LMFP / CNWs and LMFP / N-CNWs samples are 115Ω and 110Ω, respectively. This value is considered to be the total resistance of the electrode material, electrolyte resistance, and electrode lead. The slight decrease in this value may be due to the further optimization of the conductivity of LMFP by the nitrogen-doped carbon framework. In the low frequency region, the Faraday reaction plays a major role, and the impedance slope of the LMFP / N-CNWs sample is greater than that of the LMFP / CNWs sample, which has high electrochemical activity.

[0146] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A lithium manganese iron phosphate positive electrode material, characterized in that: The lithium iron manganese phosphate positive electrode material comprises a carbon frame and lithium iron manganese phosphate embedded in the carbon frame; the average particle size of the lithium iron manganese phosphate is 85nm-180nm; the porosity of the lithium iron manganese phosphate positive electrode material is 20%-36%.

2. The lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: Taking the mass fraction of the lithium iron manganese phosphate positive electrode material as 100%, the mass fraction of the lithium iron manganese phosphate is 70% to 93%.

3. The lithium iron manganese phosphate positive electrode material according to claim 2, characterized in that: The carbon framework is doped with nitrogen elements. Taking the mass fraction of the lithium manganese iron phosphate positive electrode material as 100%, the mass fraction of the nitrogen elements is 0.2% to 0.5%.

4. The lithium iron manganese phosphate positive electrode material according to any one of claims 1 to 3, characterized in that Includes at least one of the following features: (1) The specific surface area of ​​the lithium manganese iron phosphate positive electrode material is 85m 2 / g~140m 2 / g; (2) The average pore size of the lithium manganese iron phosphate positive electrode material is 30nm to 50nm; (3) The D50 particle size of the lithium manganese iron phosphate positive electrode material is 3 μm to 7.5 μm; (4) The general chemical formula of the lithium manganese iron phosphate is LiFe x Mn y PO4, wherein x is 0.2 to 0.6 and y is 0.4 to 0.

8.

5. A method for preparing the lithium iron manganese phosphate positive electrode material according to any one of claims 1 to 4, characterized in that: The steps include: S1, mixing an iron salt, a manganese salt, an organic ligand and water to obtain a first mixture; S2, subjecting the first mixture to a hydrothermal reaction, filtering, and washing to obtain a hydrothermal reaction product; S3, dispersing the hydrothermal reaction product in a first solvent to obtain a second mixture; dissolving a lithium source and a phosphorus source in the second solvent to obtain a first solution; S4, mixing the second mixture and the first solution to obtain a third mixture, stirring and drying the third mixture to obtain a solid product; S5, performing a first calcination on the solid product in a reducing atmosphere to obtain the lithium manganese iron phosphate positive electrode material.

6. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 5, characterized in that: Includes at least one of the following features: (1) The anion in the iron salt is any one of nitrate ion, nitrite ion, sulfate ion, chloride ion, bromide ion and iodide ion; (2) The anion in the manganese salt is any one of nitrate ion, nitrite ion, sulfate ion, chloride ion, bromide ion and iodide ion; (3) The organic ligand is any one of 1,4-terephthalic acid, 1,3,5-benzenetricarboxylic acid, and 1,2,4,5-pyromellitic acid; preferably, the organic ligand is 1,3,5-pyromellitic acid; (4) In S1, the mass ratio of the iron salt, the manganese salt, the organic ligand and the water is (1-2): (1-2): (0.9-1.8): (80-320).

7. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 5, characterized in that: Includes at least one of the following features: (1) The temperature of the hydrothermal reaction is 140° C. to 200° C., and the time of the hydrothermal reaction is 12 h to 15 h; (2) The washing method is: first washing with deionized water at 70°C to 90°C for 3h to 5h, and then washing with ethanol at 45°C to 75°C for 3h to 5h; (3) further purifying after washing to obtain the hydrothermal reaction product; the purification method is: washing with an ammonium fluoride aqueous solution at 60° C. to 80° C. for 3 h to 5 h; (4) The first solvent and the second solvent are each independently selected from at least one of ethanol, propanol, and n-butanol.

8. The method for preparing the lithium iron manganese phosphate positive electrode material according to any one of claims 5 to 7, characterized in that: Includes at least one of the following features: (1) The reducing atmosphere is a mixture of hydrogen and an inert gas, and the volume ratio of the hydrogen to the inert gas is 1:(4-9); (2) The temperature of the first calcination is 500° C. to 650° C., and the time of the first calcination is 5 h to 6 h.

9. The method for preparing lithium iron manganese phosphate positive electrode material according to claim 8, characterized in that: In S5, after the calcination is completed, the calcined product and C3N3(NH2)3 are dispersed in a third solvent, stirred, dried, and subjected to a second calcination under an inert atmosphere to obtain the lithium manganese iron phosphate positive electrode material; preferably, the temperature of the second calcination is 450°C to 600°C, and the time of the second calcination is 4h to 5h.

10. Use of the lithium iron manganese phosphate positive electrode material according to any one of claims 1 to 4 or the lithium iron manganese phosphate positive electrode material prepared by the preparation method according to any one of claims 5 to 9 in a lithium ion battery.

Citation Information

Patent Citations

  • Method for preparing active electrode material of lithium ion battery

    CN102593446A

  • Lithium manganese phosphate-three-dimensional carbon skeleton composite positive electrode material and preparation method thereof

    CN107689448A

  • Metal organic framework-derived phosphate composite anode material and preparation method thereof

    CN109616653A

  • Positive electrode active material, positive electrode containing positive electrode active material and lithium secondary battery

    CN109888201A

  • Carbon-coated lithium manganese iron phosphate lithium ion battery positive electrode material and preparation method thereof

    CN111477862A

Cited By

  • Lithium manganese iron phosphate composite material and preparation method thereof

    CN120637468A